Political parties or party systems?: assessing the ‘myth’ of institutionalization and democracy - Casal Bértoa, Fernando (Taylor & Francis, 2016)
No matter the region of the world under study, party (system) institutionalisation has been traditionally considered to be a necessary, but not sufficient, condition for the survival of democracy. Despite being one of the most quoted statements in the democratisation literature, the few studies looking at the relationship between institutionalisation and democratic endurance have found no evidence of the ‘almost magical’ powers of the former. This article revisits the abovementioned research question by making use of an original dataset covering all European democracies between 1848 and 2014. The main findings are threefold: (1) it is not the institutionalisation of political parties but the institutionalisation of party systems as a whole that has fostered the prospects for democratic survival in Europe; (2) there is a threshold of systemic institutionalisation which, once reached, will avoid democratic collapse; and (3) systemic over-institutionalisation does not seem to be so perilous for the survival of democracy.